The emergence of a CEE-regional multinational: A narrative of the MOL Group plc. - Zoltán Buzády (Journal for East European Management Studies, 2010)
This article describes the transition of MOL, the Hungarian Oil and Gas Company, from a state-owned enterprise to a privately owned regionalmultinational company and outlines its growth to become a leading player in the CEE region. It also illustrates how the company went through the internal restructuring process before and during its acquisition period. Over three distinct development phases it then emerged as a new species in the CEE, as a 'regional multinational'. The case also gives valuable strategic insights into the oil industry of the majority of CEE countries. – – Der Artikel beschreibt den Übergang der Ungarischen Öl- und Gasgesellschaft MOL von einem ehemaligen Staatsunternehmen zu einem modernen Wirtschaftskonzern, der als einer der ersten in Mittel- und Osteuropa zu einem 'global player' geworden ist. Es wird auch geschildert welche internen Restrukturierungsmaßnahmen vor und während der Akquisitionstätigkeit durchgeführt wurden. Die neue Spezies des 'regional multinational' entwickelte sich in diesem Fall in drei Hauptphasen. Außerdem vermittelt der Beitrag wertvolle, strategische Einsichten in das Funktionieren der Ölindustrie in den meisten der Länder Mittel- und Osteuropas.
Keywords: 650; International business; Strategic management; Regional expansion in CEE; Cross-cultural management; Change management